Effect of growth trajectories in communication skills on juvenile recidivism - Liu, Lin (Legal and criminological psychology, 2025)
Purpose Increasing numbers of children with behaviour problems in school are recognized as having language and communication difficulties. However, communication limitations have not been assessed adequately as a risk factor for juvenile recidivism. The aim of this study was to examine how changes in communication skills impacted subsequent engagement in crime among youth. Methods Four waves of longitudinal data of youth who were placed in juvenile justice residential facilities were used for the study. Group-based trajectory and multivariate regression analyses were used to investigate how the growth trajectories of communication skills impacted recidivism. Results Group-based trajectory analysis revealed heterogeneous growth in communication skills among residential youth. More interestingly, the scale of growth predicted recidivism. Conclusions This study extends an understanding of juvenile aggression and criminal offences by underlining communication limitation issues as a focal predictor of recidivism. Sufficient resources are needed for the development, evaluation and implementation of intervention programmes to help youth overcome limitations in communication.